DIFFERENCES IN pH VALUE AND SALIVARY FLOW RATE BEFORE AND AFTER CHEWING GRAPES COMPARED WITH STRAWBERRY - Herryawan; Euis Reni Yuslianti; Maghfira F. Febriani (Fakultas Kedokteran Gigi Unjani, 2022)
ABSTRACT The pH value and salivary flow rate are important factors in maintaining the balance of the oral cavity and affect the health of the teeth and mouth. When we chew foods high in water, fibre, and vitamin C, such as grapes (Vitis vinifera) and strawberries (Fragaria x ananassa), the value of these two elements can change due to stimulation. This study aims to evaluate pH levels and salivary flow rate fluctuation before and after chewing grapes in contrast to strawberries. The research method was a quasi-experimental study; forty-two research participants from Faculty of Dentistry, Universitas Jenderal Achmad Yani students. They were divided into two groups: grape and strawberries. The experiment was divided into two parts: before and after chewing the fruit. The salivary flow rate was assessed through visual screening, and salivary pH was measured using a pH meter. Data were analyzed by t-test (p<0.05). The result shows that the mean pH value and salivary flow rate increased after chewing grapes and strawberries. Compared with before chewing fruit, this increase was statistically different (p=0.000) in the two groups. Meanwhile, when the mean difference was insignificant. Chewing fruit that contains water, fibre, vitamin C, and a sour taste can increase salivary secretion, which follows the buffer system to increase salivary pH. DOI : 10.54052/jhds.v2n2.p303-316